Analysis of Factors that Influence Students' Enjoyable Learning in Class: A Literature Review - Taufiqurohman Taufiqurohman; Juntika Nurihsan; Yeni Rachmawati (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2022)
This educational approach to 21st-century teaching emphasizes a fun learning approach because it can influence students to improve the quality of their learning. Fun learning can be carried out because of the factors that influence the creation of fun learning so that students can receive stimulus from a fun learning approach and enjoy learning in the classroom in a happy and prosperous state. This research aims to comprehensively analyze the relationship between teacher creativity in presenting material, positive classroom atmosphere, and the use of technology in the learning context. The method used in this research is a literature study, a literature review analysis based on scientific articles relevant to the topic of discussion. This research shows that a fun learning approach can be created if you understand and master the factors influencing fun learning, such as pedagogical abilities, learning methods, learning media, and learning management systems. By understanding these factors, educators can create fun learning so that Students can learn happily and prosperously without feeling forced to carry out learning in class to achieve the learning objectives.